2022
DOI: 10.3390/molecules27144535
|View full text |Cite
|
Sign up to set email alerts
|

Engineered 3D-Printed Polyvinyl Alcohol Scaffolds Incorporating β-Tricalcium Phosphate and Icariin Induce Bone Regeneration in Rat Skull Defect Model

Abstract: The skull defects are challenging to self-heal, and autologous bone graft repair has numerous drawbacks. The scaffolds for the rapid and effective repair of skull defects have become an important research topic. In this study, polyvinyl alcohol (PVA)/β-tricalcium phosphate(β-TCP) composite scaffolds containing icariin (ICA) were prepared through direct-ink three-dimensional (3D) printing technology. β-TCP in the composite scaffold had osteoconductive capability, and the ICA molecule had osteoinductive capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Experimental findings demonstrated that the developed scaffolds effectively loaded and released ICA over an extended period. Furthermore, various biomaterials have been investigated to enhance the loading efficiency and bioavailability of ICA, including β-TCP [ 145 ], PLGA [ 146 ], calcium phosphate cement [ 147 ], 3D porous polydopamine/sulfonated PEEK [ 148 ], TiO 2 nanotube/PLGA [ 149 ], titanium [ 150 , 151 ], PCL/gelatin fibers [ 152 ], SF/PLCL nanofibrous scaffold [ 153 ], PLLA/PDA/chitosan [ 154 ], biphasic calcium phosphate (BCP) [ 155 ], polyvinyl alcohol (PVA)/β-TCP [ 156 ], hydroxyapatite/chitosan [ 157 ], hydroxyapatite/alginate porous composite [ 139 ], nanohydroxyapatite/polylactic acid (nHAP/PLA) [ 158 ], and PLGA/β-TCP [ 140 ].…”
Section: Icariin-loaded Nanoplatformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental findings demonstrated that the developed scaffolds effectively loaded and released ICA over an extended period. Furthermore, various biomaterials have been investigated to enhance the loading efficiency and bioavailability of ICA, including β-TCP [ 145 ], PLGA [ 146 ], calcium phosphate cement [ 147 ], 3D porous polydopamine/sulfonated PEEK [ 148 ], TiO 2 nanotube/PLGA [ 149 ], titanium [ 150 , 151 ], PCL/gelatin fibers [ 152 ], SF/PLCL nanofibrous scaffold [ 153 ], PLLA/PDA/chitosan [ 154 ], biphasic calcium phosphate (BCP) [ 155 ], polyvinyl alcohol (PVA)/β-TCP [ 156 ], hydroxyapatite/chitosan [ 157 ], hydroxyapatite/alginate porous composite [ 139 ], nanohydroxyapatite/polylactic acid (nHAP/PLA) [ 158 ], and PLGA/β-TCP [ 140 ].…”
Section: Icariin-loaded Nanoplatformsmentioning
confidence: 99%
“…The expression levels of an osteogenic gene and the genes in the Wnt signaling pathway were increased [ 139 ] chitosan/gelatin/ICA multilayer-sealed TiO 2 nanotube Physical absorption and electrochemical anodization 0.5 mg/mL In vitro Osteoblastic growth was increased and the expression of bone-related genes, such as osteopontin, type I collagen, and osteoprotegerin, was enhanced. The expression of RANKL mRNA was decreased [ 207 ] PVA/β-TCP/ICA Direct-ink 3D printing 0.4 g In vitro, in vivo Increased the adhesion and proliferation of MC-3T3-E1 cells; accelerated the in-situ bone regeneration in vivo [ 156 ] ICA-SH/BCP H 2 O 2 gas foaming 1.5 μmol In vitro, in vivo In vitro, the expression of angiogenic genes in human umbilical vein endothelial cells (HUVECs) was increased. This increase promoted the proliferation, migration, and osteoblastic differentiation of bone mesenchymal stem cells from ovariectomized rats (OVX-rBMSCs) [ 155 ] IC–CS/HA Freeze-drying 2.0 mg In vitro The stimulation of alkaline phosphatase activity and mineralized nodule formation in bone marrow-derived stroma cells was promoted [ 208 ] CPC/ICA scaffold Freeze-drying 10, 20, 40 µM In vitro, in vivo Up-regulated the expression of osteogenic and angiogenic genes in BMSCs; inhibited osteoclast; enhanced both osteogenesis and angiogenesis in the OVX calvarial defect model [ 209 ] ICA/micro/nano HAp granules Wet-chemical precipitation 200, 2000 µM In vitro, in vivo There was an increase in ALP activity and gene expression of RUNX2, Col I, OCN, and OCN protein secretion; it also caused the expression of angiogenic genes in BMSCs such as vascular endothelial growth factor (VEGF) and...…”
Section: Applications In Bone Tissue Engineeringmentioning
confidence: 99%
“…11 Through the application of a bionic extracellular matrix, this technology offers structural support that is strong enough and promotes enhanced cell adhesion. 12 Nanoattapulgite (nano-ATP) is a magnesium−aluminum silicate clay with a nanoscale rod-like crystal structure. 13 The T h i s c o n t e n t i s fundamental structural component is the stacked chain structure with nanopores and surface-active groups.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The nonheated liquefaction technology of extrusion 3D printing allows for the preparation of materials without affecting their biological activity and the creation of composite scaffolds by adding dopants . Through the application of a bionic extracellular matrix, this technology offers structural support that is strong enough and promotes enhanced cell adhesion …”
Section: Introductionmentioning
confidence: 99%
“…↑ proliferation, differentiation of osteoblasts, bone mineralization ↓ cell apoptosis direct osteoblast stimulation: activation of the bone morphogenetic protein (BMP) cascade through (promoting Runx2/Cbfa1 expression and the production of BMP-4, BMP-2, and SMAD4 and nitrous oxide release; high levels of ALP suppression of p38 and JNK pathways in the osteoclasts, ↓ release of prostaglandinEpimediumIn vivo (rats)[61,62] ↓ bone loss in the median bone area by regulating the ratio between osteoprotegerin and RANKL, which are key mediators of osteoclast genesis. ↑ proliferation, differentiation of osteoblasts, bone mineralization ↓ cell apoptosis direct osteoblast stimulation: activation of the bone morphogenetic protein (BMP) cascade through (promoting Runx2/Cbfa1 expression and the production of BMP-4, BMP-2, and SMAD4 and nitrous oxide release; high levels of ALP suppression of p38 and JNK pathways in the osteoclasts, ↓ release of prostaglandin E2 by osteoblasts => inhibition of osteoclast differentiationEpimediumIn vivo (rats)[63] [64]…”
mentioning
confidence: 99%